On the plain of snakes : a Mexican journey - Theroux, Paul (Houghton Mifflin Harcourt, 2019)
"Legendary travel writer Paul Theroux fearlessly drives the entire length of the US-Mexico border, then goes deep into the hinterland, on the back roads of Chiapas and Oaxaca, to uncover the rich, layered world behind today's brutal headlines."--Provided by publisher.